Unveiling the Insular Lobe of Reil: Neurophysiological and Anatomical Features - Damiani, Daniel; Nascimento, Ana Maria; Pires, Vanessa Gonçalves (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
The insular lobe has long been investigated, from its anatomical descriptions to its neurophysiological activity. Located in a central location, the insular lobe participates in several afferent and efferent pathways, forming part of the eloquent and fundamental structures that make up the central core of the brain. The lobe of the insula has participation in language function, such as speech, sensory (e.g., taste), limbic, autonomic (visceral), also forming part of complex associative circuits, including part of the circuits of mirror neurons. Several functional descriptions attributed to the insular lobe have been made in patients suffering from cerebrovascular diseases, as well as in those with epilepsy. Much progress and many descriptions have also been made in patients with tumors. Despite much information already available about the insular lobe, it is likely that much will be discovered in the coming years.
Keywords: insular lobe; central core of the brain; insular neurophysiology; insular neurocircuitry